Engineering optical tools for remotely controlled brain stimulation and regeneration. (22nd March 2023) - Rodrigues, Artur Filipe; Rebelo, Catarina; Reis, Tiago; Simões, Susana; Bernardino, Liliana; Peça, João; Ferreira, Lino
Abstract : This review covers the latest progress in the application of light-responsive nanomaterials for on-demand drug delivery to the brain and for neuromodulation, with the aim of achieving brain stimulation and regeneration. Abstract : Neurological disorders are one of the world's leading medical and societal challenges due to the lack of efficacy of the first line treatment. Although pharmacological and non-pharmacological interventions have been employed with the aim of regulating neuronal activity and survival, they have failed to avoid symptom relapse and disease progression in the vast majority of patients. In the last 5 years, advanced drug delivery systems delivering bioactive molecules and neuromodulation strategies have been developed to promote tissue regeneration and remodel neuronal circuitry. However, both approaches still have limited spatial and temporal precision over the desired target regions. While external stimuli such as electromagnetic fields and ultrasound have been employed in the clinic for non-invasive neuromodulation, they do not have the capability of offering single-cell spatial resolution as light stimulation. Herein, we review the latest progress in this area of study and discuss the prospects of using light-responsive nanomaterials to achieve on-demand delivery of drugs and neuromodulation, with the aim of achieving brain stimulation and regeneration.